Porous framework materials for capture and storage - Bai, Linyi (2018)
Porous framework materials have been widely studied, due to their numerous attracted intrinsic properties. With the extensive development of this field, incorporating exotic functional anchors have become a new theme to enrich and develop the usage of such materials, which inspires much interest of fabricating hierarchical materials. The implantation of multiple functional anchors to host framework materials not only brings attracting structural backbone and physical properties but also opens new routes for the extensive development of such materials in chemistry, material science and engineering. The primary focus of this thesis has been made to compare the recent advancements of porous framework materials in structure and post-functionalization, and analyse their advantages and disadvantages in structural design and application performance so that some critical challenges can be summarized and research motivation can be thus inspired. Next, our three-works related to the porous framework materials design based on the above analysis were introduced and discussed in details, ranging from the decoration of structure, to external polymer incorporation, and to improve its conductivity via conjugated bonding. Subsequently, summary and outlook in this rapidly developing area are finally discussed. Clearly, such unique porous framework materials will continue to attract the increasing attention, and the display stage will be offered to them in future, owing to their superior application potential.